‘The opposite of a history’: What substance use in pregnancy can lend to an ethics of accompaniment (Medicine Anthropology Theory, 2015)
Theoretical work in critical medical anthropology and biomedicine on substance use in pregnancy has yet to develop a cohesive framework of the maternal-fetal unit (MFU) as a dynamic object. As a result, patient history, risk, and agency continue to be driven by an Enlightenment-era, monolithic conception of individual will. I use the example of Carla, a young woman actively using heroin in her pregnancy, to illustrate the limits of the MFU as it is currently conceived. By using critiques of subjective utilitiarianism, as discussed by Byron Good, and the concept of becoming, as elucidated by Gilles Deleuze and Félix Guattari, this article seeks to articulate an ethics of accompaniment, focused on both individual patient care and wider sociopolitical advocacy. These ethics help to redefine the MFU, and support new and unique ways of providing services to this often marginalized and vulnerable population.